Cover Feature: Designation of a Nano‐Fe3O4 Based Composite Electrode with Long Cycle Life for Lithium‐Ion Batteries (ChemElectroChem 14/2019). Issue 14 (24th June 2019) - Wu, Pengfei; Dong, Xichao; Gu, Chong; Ge, Shuaipeng; Su, Zhiming; Lu, Yingxi; Guo, Changqing; Shao, Guangyu; Zhong, Yunwang; Liu, Anhua
Abstract : The Cover Feature shows carbon and SiC double‐shell coated SiO x /Fe3 O4 (Fe x Si y ) heterojunction nanocomposites, which are fabricated by using a simple method that is expected to be widely applied to the preparation of other nanoparticles. These nanocomposites demonstrate excellent performance and cycle life over 2500 cycles in lithium‐ion battery testing, which can be attributed to its unique composite structure of various materials and its small particle size. More information can be found in the Article by P. Wu et al. on page 3606 in Issue 14, 2019 (DOI: 10.1002/celc.201900250 ).